The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1093/eurpub/ckp148
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cannabis use trajectories, grade repetition and family background on the school-dropout rate at the age of 17 years in France

Abstract: Cannabis use is rarely a trigger for grade repetition but can have either damaging or positive effects on school attainment depending of the level of use. Positive social competence reflected by peer initiation should be investigated to understand this paradoxical effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
3
19
0
12
Order By: Relevance
“…These patterns are consonant with literature indicating that cigarette smokers over time, especially young cigarette smokers, are becoming increasingly prone to externalizing behaviors (Chassin et al, 2007; Legleye et al, 2010; Little et al, 2008). Similar overall patterns were observed for the internalizing disorders, although it should be noted that for both GAD and MD, rates among the two smoking groups increased across initial cohorts then held constant, and in the final cohort, decreased.…”
Section: Discussionsupporting
confidence: 88%
“…These patterns are consonant with literature indicating that cigarette smokers over time, especially young cigarette smokers, are becoming increasingly prone to externalizing behaviors (Chassin et al, 2007; Legleye et al, 2010; Little et al, 2008). Similar overall patterns were observed for the internalizing disorders, although it should be noted that for both GAD and MD, rates among the two smoking groups increased across initial cohorts then held constant, and in the final cohort, decreased.…”
Section: Discussionsupporting
confidence: 88%
“…Results about school were consistent with former research, which showed that leaving school without qualification was linked to prior cannabis use (Fergusson et al, 2003), and early initiation of cannabis use with subsequent use (Legleye et al, 2009), while school connectedness was associated with less frequent cannabis use (Resnick et al, 1997). We found that teenagers who indicated they did not like school at all were nearly twice as at risk for cannabis experimentation.…”
Section: Interpretation Of the Findingssupporting
confidence: 89%
“…Cannabis consumption also was linked to low academic performance (Cox, Zhang, Johnson, & Bender, 2007) and increased risk of leaving school without qualification (Fergusson, Horwood, & Beautrais, 2003). Cannabis initiation before 14 with subsequent daily use was associated with school dropout at 17 (Legleye et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In France, Huerre and Leroy [6] presented a holistic analysis of school dropout, Brandibas [7] considered truancy to be associated with different types of anxiety, whereas Legleye [8] reported an association between dropout and the progression to daily cannabis use. Jonsson [9] pointed out that Swedish adolescents suffering from depression were less likely than their non-depressed peers to have graduated from higher education.…”
Section: Introductionmentioning
confidence: 99%